NUTQI TO‘LIQ RIVOJLANMAGANLIK (NTR) BOLALAR BILAN OLIB BORILADIGAN O‘YINLAR TEXNOLOGIYASI (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the characteristics of preschool children with Underdeveloped Speech (UDS), analyzing the linguistic, cognitive, and neuropsychological factors affecting delayed speech development. The study highlights the three developmental levels of UDS, diagnostic indicators, and corrective pedagogical strategies. The effectiveness of play-based technologies is discussed, demonstrating how structured games and exercises enhance lexical, grammatical, and phonemic skills, while supporting the neurofunctional growth of speech. Early intervention and individualized multisensory approaches are emphasized as crucial for improving speech competence, communicative readiness, and social adaptation.